FinTech adoption and bank financial performance in emerging markets: evidence from panel data analysis - Dr. S. Ramesh (HM Journals, 2026)
The rapid proliferation of financial technology (FinTech) has fundamentally reshaped the global banking landscape, compelling traditional commercial banks in emerging economies to reassess their operational strategies and performance benchmarks. This study investigates the impact of FinTech adoption on the financial performance of commercial banks in selected emerging market economies — specifically Pakistan, Vietnam, and Kenya — over the period 2013 to 2022. Employing a dynamic panel data methodology using the System Generalized Method of Moments (GMM) estimator, we analyse the relationship between FinTech development proxies — including digital payment penetration, mobile banking adoption rates, and peer-to-peer (P2P) lending volumes — and key bank performance indicators such as Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Cost-to-Income Ratio (CIR). Based on a balanced panel of 87 commercial banks, our results reveal that FinTech adoption exerts a statistically significant positive effect on ROA and ROE for small-to-medium-sized banks, while large banks experience a complementary effect primarily through ROE. Mobile banking penetration is found to be the most consistent driver of improved operational efficiency, as reflected in a declining Cost-to-Income Ratio. However, rising P2P lending volumes are associated with modest net interest margin compression in the medium term, suggesting competitive displacement of traditional lending activities. The findings carry important implications for bank management, FinTech regulators, and policymakers seeking to harness digital financial innovation without undermining banking sector stability.